Sequence variation in mitochondrial complex I genes: mutation or polymorphism?. Issue 2 (21st June 2005) - Mitchell, A L; Elson, J L; Howell, N; Taylor, R W; Turnbull, D M
Abstract : Background: Defects of the mitochondrial genome are recognised as common causes of genetic disease. Sequencing of large portions or even the entire mitochondrial genome is routine in many laboratories for the investigation of mitochondrial disease. However, establishing whether a detected sequence change is polymorphic or pathogenic is still a major difficulty because of its highly polymorphic nature. This has major implications for the patient and the family. Objective: To describe a scoring system for determining the likelihood that a given sequence variant in one of the seven mitochondrially encoded complex I ( MTND ) genes is truly pathogenic. Results: The scoring system was applied to 50 reported MTND mutations. Using this system, 21 of the mutations analysed fell into the group of neutral sequence variants, 10 were classified as possibly pathogenic, three as probably pathogenic, and 16 as almost certainly pathogenic. Conclusions: The proposed scoring system should advance the interpretation of sequence variants and ensure that candidate pathogenic mutations are rigorously investigated.